Consumer perspective of omnichannel commerce = Omnichannel commerce z punktu widzenia konsumenta - Kaczorowska-Spychalska, Dominika (Zielona Góra: Faculty of Economics and Management Press)
The evolution of hypermedia space and growing saturation of the market with mobile devices, an increasing role of Big Data, which allow for multidimensional analysis of data from offline and online markets, growing popularization of solutions of Market Intelligence supported by Cloud Computing technology as wells development of potential and opportunities of adapting the Artificial Intelligence (AI) and Internet of Things (IoT) in commerce cause that customers and their experience become a major point of activity of companies/brands.
Keywords: omnichannel commerce; handel detaliczny; konsument; Internet of Things (IoT); retail trade; customer